2018
DOI: 10.15587/1729-4061.2018.126358
|View full text |Cite
|
Sign up to set email alerts
|

Substantiation of the mechanism of interaction between biopolymers of rye­and­wheat flour and the nanoparticles of the magnetofооd food additive in order to improve moisture­retaining capacity of dough

Abstract: Обґрунтовано механізми вологоутримуючої здатності наночасток (НЧ) поліфункціональної харчової добавки «Магнетофуд» в житньо-пшеничному тісті. Розглянуто механізми взаємодії НЧ харчової добавки «Магнетофуд» з водою у середовищах з різним Рh, а також механізми взаємодії НЧ «Магнетофуд» з іоногеннимі групами білків, ліпідів, вуглеводів житньо-пшеничного борошна. Запропонована «кластерно-петельно-ланцюгова» модель взаємодії харчової добавки «Магнетофуд» з біополімерами житньо-пшеничного борошна Ключові слова: полі… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…Earlier studies [12,13] have demonstrated that the most intensive chemical and electrostatic interaction between nanoparticles (NP) of «Magnetofood» and dipoles of H 2 O and ionogenic groups of biopolymers occurs in acidic medium.…”
Section: Results Of Research Into the Mechanism Of Interaction Betweementioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies [12,13] have demonstrated that the most intensive chemical and electrostatic interaction between nanoparticles (NP) of «Magnetofood» and dipoles of H 2 O and ionogenic groups of biopolymers occurs in acidic medium.…”
Section: Results Of Research Into the Mechanism Of Interaction Betweementioning
confidence: 99%
“…NP of «Magnetofood» food supplement has high-power energy and chemical potential, and bio-relation to biopolymers, namely, proteins, carbohydrates. Therefore, they bear new functional and technological properties, for example, MRA [7,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The structure-forming ions in the food additive "Magnetofood" are the ferrum cations Fe 2+ and Fe 3+ . The high tension of the electric field generated by the ions of ferrum from the nanoparticles of the additive enhances the polarization of molecules in the compounds of food systems, which contributes to their additional ordering outside the surface of the particles, as well as adsorption [7][8][9]. Nanoparticles in the food additive "Magnetofood" have the high energy and chemical potential and the bio-affinity to biopolymers, specifically proteins, carbohydrates, and are characterized by new functional and technological properties: structure-forming, stabilizing, emulsifying, water-binding, water-retaining.…”
Section: T S Y K H a N O V S K Amentioning
confidence: 99%
“…We have designed and proposed the food additive "Magnetofood" as an improving additive to food systems. In food systems, "Magnetofood" demonstrates the antioxidant, sorption, bacteriostatic, complex-forming, emulsifying, moisture-retaining, moisture-binding, stabilizing, and structure-forming properties [7][8][9].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation